Research of the Influence of Speed Adjustment Strategy on Drivability Under the Baking Energy Recovery Condition of an Electric Vehicle Equipped with EM-CVT - Ye Ming; Li Si; Dai Jun; Ma Xiang (Jixie chuandong)
Taking an electric vehicle equipped with EM-CVT as the research objects,the research of weak drivability and optimization of control strategy are carried out under the impact of EM-CVT in braking energy recovery condition,which on the basis of confirming vehicle transmission scheme,vehicle parameters and control strategy. By analyzing longitudinal dynamics in the braking process,it turns out that CVT ratio and the changing rate of speed ratio are the influence factor to drivability under the impact of EM-CVT in baking energy recovery condition. Firstly,the weak drivability and the control strategy of original vehicle are explained,the relationship with drivability influence factor is analyzed,and speed adjustment strategy of the EM-CVT is optimized. The result shows that,the intervention process of regenerative brake is slow down,and the speed ratio in regeneration baking process and speeding up process is well matched,without large fluctuations,and the objective of optimized vehicle drivability is achieved.